The Principal Navigations, Voyages, Traffiques, and Discoveries of The English Nation $1 (BVolume 12 :s America, Part I - Hakluyt, Richard, 1552?-1616; Goldsmid, Edmund (Salt Lake City, UT : Project Gutenberg, 2004)
"The Principal Navigations, Voyages, Traffiques, and Discoveries of The English..." by Richard Hakluyt is a historical account compiled in the late 16th century. This collection extensively chronicles the maritime explorations and trade endeavors of the English, focusing particularly on the discoveries related to the New World, known today as America. The book serves as a testament to the age of exploration, detailing the voyages undertaken by figures like John Cabot and others in their quest for trade routes and new lands. At the start of this work, Richard Hakluyt offers an introduction that outlines the significance of the voyages undertaken by the English in discovering new territories. He emphasizes the importance of documenting these expeditions for historical record and the betterment of navigation knowledge. The opening also discusses the early voyages of Madoc, a Welsh prince reputed to have discovered parts of America before Columbus, setting the stage for the account of later, more well-documented explorations. The text is rich with references to classical authors and ancient philosophies, lending credibility to Hakluyt's claims about the New World and its potential for wealth and colonization. (This is an automatically generated summary.)
Release date is 2004-10-05
Produced by Karl Hagen and the Project Gutenberg Online Distributed Proofreaders
Keywords: Voyages and travels; Discoveries in geography -- English